Tingkat Penerimaan panelis Terhadap Yoghurt Dengan Perlakuan Lama Fermentasi, Jenis susu dan Lama penyimpanan yang Berbeda - Tursina Tursina; Irfan Irfan; Sri Haryani (Jurnal Ilmiah Mahasiswa Pertanian, 2019)
Abstrak: Susu didefinisikan sebagai salah satu bahan pangan bernutrisi tinggi yang baik berperan sebagai asupan penting untuk, pertumbuhan kesehatan dan kecerdasan. Walaupun susu memiliki nilai gizi yang sangat baik namun untuk sebagian orang konsumsi dapat menimbulkan masalah berupa terjadinya lactose intolerance yaitu ketidakmampuan tubuh untuk mencerna laktosa yang terdapat didalam susu. Hal ini dapat diatasi dengan mengubah laktosa menjadi glukosa dan galaktosa dengan cara fermentasi. Salah satu produk fermentasi berbasis susu adalah yoghurt. Penelitian ini bertujuan untuk mempelajari pengaruh  lama fermentasi dan jenis susu yang digunakan dalam pembuatan yoghurt terhadap sensori yoghurt selama masa penyimpanan. Penelitian ini dilakukan menggunakan Rancangan Acak Kelompok (RAK) yang terdiri dari 3 faktor, faktor pertama yaitu lama fermentasi (F) yang terdiri dari 2 taraf, yaitu: F1 = 10 jam, F2 = 16 jam. Faktor kedua yaitu jenis susu yang digunakan yang terdiri dari 2 taraf, yaitu: S1 = susu sapi dan S2 = susu kambing. Faktor ketiga yaitu lama penyimpanan yang terdiri dari 3 taraf, yaitu: P1 = 0 minggu, P2 = 2 minggu, P3 = 4 minggu. Analisis yang dilakukan adalah uji organoleptik secara hedonik meliputi atribut warna, aroma, rasa dan tekstur. Hasil uji organoleptik (hedonik) menunjukkan bahwa secara umum panelis lebih menyukai yoghurt perlakuan jenis susu sapi dengan fermentasi 10 jam dan lama penyimpanan 3 hari (minggu ke-0). Abstract: Milk is determined as one of the high nutritious kind of foods that are good for important consumption, health and intelligence growth. Because milk has a very good nutritional value for most people who can spend problems because of lactose intolerance which is the body's inability to digest lactose in milk.This problem can be overcome by converting lactose to glucose and galactose by fermentation. One of the milk-based fermented products is yogurt. This study aims to investiage the effect of fermentation time and the type of milk used in making yogurt on the sensory yogurt during the storage period. This study was conducted using a Randomized Block Design (RBD) consisting of 3 factors, the first factor was the duration of fermentation (F): F1 = 10 hours, F2 = 16 hours. the second factor was the type of milk used which consists of twolevels, namely: S1 = cow's milk and S2 = goat's milk. The third factor is the storage time which we: P1 = 0 weeks, P2 = 2 weeks, P3 = 4 weeks. the analysis carried out were a hedonic test covering attributes of color, aroma, taste and texture. The organoleptic (hedonic) test result showed that in general all panelists preferred yogurt which was made by cow milk with 10 hours fermentation and 3 days of storage time (week 0).Abstract: Milk is determined as one of the high nutritious kind of foods that are good for important consumption, health and intelligence growth. Because milk has a very good nutritional value for most people who can spend problems because of lactose intolerance which is the body's inability to digest lactose in milk.This problem can be overcome by converting lactose to glucose and galactose by fermentation. One of the milk-based fermented products is yogurt. This study aims to investiage the effect of fermentation time and the type of milk used in making yogurt on the sensory yogurt during the storage period. This study was conducted using a Randomized Block Design (RBD) consisting of 3 factors, the first factor was the duration of fermentation (F): F1 = 10 hours, F2 = 16 hours. The second factor was the type of milk used which consists of two levels, namely: S1 = cow's milk and S2 = goat's milk. The third factor is the storage time which we: P1 = 0 weeks, P2 = 2 weeks, P3 = 4 weeks. The analysis carried out were a hedonic test covering attributes of color, aroma, taste and texture. The organoleptic (hedonic) test results showed that in general all panelists preferred yogurt which was made by cow milk with 10 hours fermentation and 3 days of storage time (week 0).